Optimization of Moodle-based Learning Management System in Sociology Learning: A Differentiated Approach Analysis - Fahma Fitroti; Saliman Saliman; Anik Widiastuti; Agustina Tri Wijayanti (Yayasan Keluarga Guru Mandiri, 2025)
Sociology learning requires critical, analytical, and reflective thinking, which is often not fully supported by traditional teaching methods. Differentiated learning offers a way to address diverse student needs, and Moodle, as a Learning Management System (LMS), provides a potential platform to support this approach. This study aims to examine how Moodle can optimize differentiated learning in Sociology subjects. Using a quantitative descriptive method, data were collected from 176 students of grades XI and XII majoring in Sociology at SMAN 1 Jogonalan, selected through simple random sampling. The instrument was an online questionnaire with closed-ended Likert scale items and open-ended questions to explore challenges. Descriptive statistical analysis revealed that 48.30% of students rated their Moodle use as high, 26.14% as medium, and 25.57% as low. Students perceived Moodle as useful in increasing learning flexibility, supporting concept understanding, and accommodating individual learning styles. However, limitations were also identified, including insufficient infrastructure and a lack of digital proficiency. The study concludes that Moodle has the potential to strengthen differentiated learning in Sociology. The findings contribute to the development of technology-based learning strategies in secondary education and underscore the need for additional support and training to facilitate effective LMS implementation.